Cryptocurrencies and the future of money. Money and trust in the UK - Seiferling, Mike; Ahmed, Thamin; ElBahrawy, Abeer Yehia; Chan, Keith; Padilha, Tales (IE Center for the Governance of Change, 2020)
Much like the US Dollar, the British Pound has a unique place in the world. The is largely due to a combination of a long lived and “robust institutional framework” and the sterling’s monopoly as legal tender in the UK which “sets a very high bar for competing forms of money to dislodge sterling.” (Mark Carney, Governor of the Bank of England)1 . We can see evidence of this responsibly managed money growth in the fiat currency era and stable inflation in the figures below.
Keywords: Cryptocurrency; Criptomonedas; Policies; Políticas; Perspectives; Perspectivas; Disrupting economy; Economía disruptiva